The challenge of broadcasting parliamentary proceedings - Inter-Parliamentary Union; European Broadcasting Union; Association of Secretaries General of Parliaments; Inter-Parliamentary Union; European Broadcasting Union; Association of Secretaries General of Parliaments
Contents include: Introduction -- Messages -- The role of public broadcasters -- Examples of different channels -- Comments from the floor -- Questions & Answers -- EBU proposes programme exchanges -- Survey -- Conclusions .